Application of Whole Genome Sequencing Technology in the Investigation of Genetic Causes of Fetal, Perinatal, and Early Infant Death. (January 2018) - Armes, Jane E; Williams, Mark; Price, Gareth; Wallis, Tristan; Gallagher, Renee; Matsika, Admire; Joy, Christopher; Galea, Melanie; Gardener, Glenn; Leach, Rick; Swagemakers, Sigrid MA; Tearle, Rick; et al.
Death in the fetal, perinatal, and early infant age-group has a multitude of causes, a proportion of which is presumed to be genetic. Defining a specific genetic aberration leading to the death is problematic at this young age, due to limited phenotype–genotype correlation inherent in the underdeveloped phenotype, the inability to assess certain phenotypic traits after death, and the problems of dealing with rare disorders. In this study, our aim was to increase the yield of identification of a defined genetic cause of an early death. Therefore, we employed whole genome sequencing and bioinformatic filtering techniques as a comprehensive, unbiased genetic investigation into 16 fetal, perinatal, and early infant deaths, which had undergone a full autopsy. A likely genetic cause was identified in two cases (in genes; COL2A1 and RYR1 ) and a speculative genetic cause in a further six cases (in genes: ARHGAP35, BBS7, CASZ1, CRIM1, DHCR7, HADHB, HAPLN3, HSPG2, MYO18B, and SRGAP2 ). This investigation indicates that whole genome sequencing is a significantly enabling technology when determining genetic causes of early death.